PENERAPAN TEKNIK NUMBERED HEADS TOGETHER (NHT) DALAM PENINGKATAN PEMBELAJARAN BILANGAN PECAHAN SISWA KELAS V SD - PGSD, Winarsih (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: Application of Numbered Heads Together (NHT) Technique in Increasing Fraction Number Learning of 5th Grade Students Elementary School. The purpose of this research to increase fraction number learning of fifth grade students elementary school by application of Numbered Heads Together technique. This research is a collaborative classroom action research. This study was conducted in 3 cycles. Each cycle consist of planning, action, observation, and reflection. Subjects were all students in the fifth grade elementary school. Data come from students, teacher, and observer. Data collection techniques are test techniques and non test techniques. The validity of the source data using triangulation techniques and triangulation of data collection techniques. The conclusions of this research is the application of Numbered Heads Together technique can increase fraction number learning of fifth grade students elementary school. Keywords: NHT?s technique, increase learning, fraction number Abstrak: Penerapan Teknik Numbered Heads Together (NHT) dalam Peningkatan Pembelajaran Bilangan Pecahan Siswa Kelas V SD. Tujuan penelitian ini adalah untuk meningkatkan pembelajaran bilangan pecahan siswa kelas V SD dengan penerapan teknik Numbered Heads Together. Penelitian ini merupakan penelitian kolaboratif yang dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari tahap perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini adalah siswa kelas V SD. Sumber data penelitian ini adalah siswa, guru, dan observer. Teknik pengumpulan data dilakukan dengan teknik tes dan non tes. Validitas data menggunakan teknik triangulasi sumber dan triangulasi pengumpulan data. Simpulan penelitian adalah penerapan teknik Numbered Heads Together dapat meningkatkan pembelajaran Bilangan Pecahan siswa kelas V SD. Kata kunci: teknik NHT, Peningkatan pembelajaran, Bilangan Pecahan